Liquid biopsy detection of tumor shed in cancers for which molecular profiling is best practice. Issue 28 (1st October 2022) - Kasi, Pashtoon Murtaza; Weipert, Caroline; Kaylor, Julie
Abstract : 412 Background: Technology and innovation in genomic profiling provides an opportunity to improve the outcomes of advanced solid cancer patients including some cancer agnostic approved therapies, and biomarker analysis is recommended within NCCN guidelines for 15 solid cancers. Tissue-based molecular profiling may not be efficient or feasible for many patients due to factors such as fitness for procedure, timeliness to treatment, and sample exhaustion, leading to healthcare disparities. Despite robust validation and regulatory approval for use in genomic profiling across all advanced solid tumors, circulating tumor DNA (ctDNA) or "liquid biopsy" is included within NCCN guidelines for 9 solid cancers. The utility of ctDNA based profiling in additional cancers for which molecular analysis is recommended is contingent upon the ability to reliably detect tumor shed and biomarkers of interest. Methods: Results were analyzed for a large nationwide cohort over 40, 000 patients seen across community and academic settings receiving Guardant360 CDx or Guardant360 (Guardant Health, Redwood City, CA) in a 6-month window to evaluate detection of ctDNA, or tumor shed, among cancers for which guidelines do and do not currently include liquid biopsy. Results: Tumor shed was detected in 83%-92% (median 89%) of cancers for which guidelines include liquid biopsy, and 73%-94% (median 88%) for those without guideline inclusion for liquid biopsy. The detection of tumor shed was similar among cancer types with and without liquid biopsy inclusion in guidelines (p value = 0.5014; two-tailed t-test). Conclusions: The non-invasive nature of liquid biopsy, rapid turnaround, and sufficient tumor shed (as shown by results of this study) further support the inclusion of liquid biopsy in NCCN guidelines when molecular profiling is indicated. For tumors where it may replace the need for tissue biopsy acquisition, a plasma-first approach incorporating a liquid biopsy can reduce the financial toxicity as it would be more efficient and cost-effective. ctDNA detected, % Guidelines recommend liquid biopsy CRC 92% Lung 91% Urogenital, Male 90% Breast 89% Pancreatic Adenocarcinoma 89% Gastric/Esophageal 87% Skin 83% Guidelines recommend molecular profiling but do not include liquid biopsy Bladder 94% Ovarian 94% Cholangiocarcinoma 92% Other GI 92% CUP 91% Endometrial 91% Cervix 88% Other 88% Head & Neck 85% Kidney 82% GIST 80% Bone/Soft Tissue 80% Thyroid 73%